A reforma agrária como uma política pública de desenvolvimento ou política social? Uma análise a partir dos assentamentos rurais Tereza do Cedro e Dandara no município de Uberaba/MG - Masson, Gabriela Abrahão [UNESP] (2016)
According to Barbosa (2012), Brazil has one of the biggest land concentration in the world. Only 0,8% of land owners have possession of 31,6% of arable lands. It is estimated that promoting a land reform, which would raise the decentralisation of land structure in Brazil, would directly benefit 2,5 million of landless families. Land reform, thus, as a public policy of development, together with either agricultural and social policies, could trigger a rural development process in Brazil, sustained not only by an agricultural development. On the other hand, it is known that the social, political, economical, therefore historical options made by the earlier Brazilian governments on land reform now lead to a “non-land reform”, according to Oliveira (2011). Thereby, much more than a dispossession policy is expected for solving the social inequality that follows the rise of the country, with public policies that may contribute and enhance the sojourn of settled people in the rural settlements. In this thesis, we aim to question, discuss and think over the land reform ongoing in Uberaba, and if it can be whether characterized as a public policy of development or becomes an increasingly selective, focused and compensatory social policy. Therefore, a bibliographic, documental research was made, which enabled a theoretical practical essential improvement for the reflective process of the information obtained on field research and on participant observation. The following settled people of land reform who live in the rural settlements were interviewed by semi-structured interviews: Political leadership, Uberaba’s secretary of agriculture, livestock, fishing and apiculture and the state superintendent of Incra of Minas Gerais. The data analysis were based on qualitative methodology and the materialistic historical dialectic method of apprehension of reality enabled consecutive approaches to the unique situation studied. It allowed us to seize that the constitution of the rural settlements studied has many contradictions that enforced numerous challenges to the settled people current routine. Thus, the ongoing land reform in the settlements is still a procedure that is in force and is affected by structural elements of Brazilian reality, which daily invalidate the land reform process as a public policy of development. However, the tone of class struggle for peasants and landless workers in these settlements is the promise for possible better conditions of life and work.